Wavelets Convergence and Unconditional Bases for Lp(ℝn) and H1(ℝn). (5th February 2014) - Kumar, Devendra
Abstract : We prove that reasonable nice wavelets form unconditional bases in function space other thanL 2 ( ℝ n, X ) . Moreover, characterization of convergence of wavelets series inL p ( ℝ n, X ) space and Hardy spaceH 1 ( ℝ n, X ) has been obtained. Here, X is a Banach space with boundedness of Riesz transform.